Acute Effects of Cigarette Smoke Extract on Alveolar Epithelial Sodium Channel Activity and Lung Fluid Clearance - Downs, Charles A. (American Thoracic Society, 2013)
Cigarette smoke contains high levels of reactive species. Moreover, cigarette smoke can induce cellular production of oxidants. The purpose of this study was to determine the effect of cigarette smoke extract (CSE)-derived oxidants on epithelial sodium channel (ENaC) activity in alveolar type 1 (T1) and type 2 (T2) cells and to measure corresponding rates of fluid clearance in mice receiving a tracheal instillation of CSE. Single-channel patch clamp analysis of T1 and T2 cells demonstrate that CSE exposure increases ENaC activity (NPo), measured as the product of the number of channels (N) and a channels open probability (Po), from 0.17 ± 0.07 to 0.34 ± 0.10 (n = 9; P = 0.04) in T1 cells. In T2 cells, CSE increased NPo from 0.08 ± 0.03 to 0.35 ± 0.10 (n = 9; P = 0.02). In both cell types, addition of tetramethylpiperidine and glutathione attenuated CSE-induced increases in ENaC NPo. Biotinylation and cycloheximide chase assays indicate that CSE-derived ROS increases channel activity, in part, by maintaining cell surface expression of the α-ENaC subunit. In vivo studies show that tracheal instillation of CSE promoted alveolar fluid clearance after 105 minutes compared with vehicle control (n = 10/group; P < 0.05).